Acceptance testing of a CT scanner with a knowledge-based iterative reconstruction algorithm (Brazilian Journal of Radiation Sciences, 2019)
Implementation of efficient computed tomography (CT) detectors, automatic exposure control and iterative reconstruction algorithms allows to obtain high quality images while minimizing absorbed dose to the patients, in consonance with the ALARA criterion. In this work, we present the results of the acceptance testing of a Philips iCT Elite scanner with the IMR reconstruction algorithm. A Catphan 500 phantom was used for this purpose. RESULTS: The laser positioning system was misaligned, while the gantry and table were aligned. The high-contrast spatial resolution was 21 lp/cm. Regarding low contrast resolution, a 3 mm pin with 0.3% contrast was observed using IMR for CTDIvol = 10.4 mGy, while a 5mm pin was observed using filtered back projection (FBP). Average uniformity was ± 3 Hounsfield Units (HU) and noise was